Slægten Goldkette - en jødisk cirkusfamilie - Falk, Allan (Rambam. Tidsskrift for jødisk kultur og forskning, 2023)
Circus is not a trade many people connect with Jews. But Jewish artists existed in Europe for hundreds of years, and the descendants of one of them had special connections to Denmark. His name was Levi and he was a tight-rope dancer. He performed at the crowning of the Austrian queen Maria Theresia in 1740 and was rewarded with a gold chain – in German Goldkette – and his descendants have used that word as their family name ever since. A grandchild, Wulff Levi (called Louis) Goldkette, was supposedly born in Copenhagen in 1778. He was also a tight-rope dancer, but furthermore he performed as a magician. His son, Hartwig Goldkette, grew up and continued his father’s work, himself becoming an excellent circus rider. He settled in Rendsburg in Schleswig-Holstein and arranged tours from there, especially in Denmark. He was married to Mine Goldstein, whose mother was Zerle Blumenfeld. Circus Blumenfeld became one of the most well-known circuses of Europe, but based in Germany many of their family members were murdered during the Holocaust. This marriage, however, was only one of many between members of different Jewish circus families. In the Dutch-Jewish circus family of Goudsmit, three siblings engaged in such marriages: Betje Goudsmit married Hartwig’s brother Herman, her brother Joseph married Hartwig’s daughter Jeanette, and her sister Jeanette married Hartwig’s son Louis. Despite their family connection, Louis and Joseph Goudsmit owned each their own circus, and they both had many appearances in Denmark, as advertisements in local papers show. Louis Goldkette can also be found in Danish censuses in 1870 in the town of Faaborg and in 1880 in the town of Aarhus with his family, consisting of his wife Jeanette and their 10 children. The birthplaces of the family members – which are mentioned in censuses – give a good impression of how circus life meant wandering from place to place. Hartwig and Herman had a half brother, born with the name of Wulff Goldkette in 1816 in Naestved, Zealand (Denmark). His mother was a young girl, Elisabeth Funk, who at the age of eight had been sold to Louis Goldkette (the elder) for 100 Thaler, to learn the work of a circus artist. At the age of 15 she became pregnant, and Louis Goldkette – at that time 22 years her senior – was undoubtedly the father. The little boy was at the age of one given to the care of a bricklayer in Faaborg, Lars Soerensen. The parents were supposed to fetch the boy after two years, but they never returned. At the age of 14, the boy was baptized and got the name of Frederik Christian Soerensen, and he became a bricklayer like his foster father. Most of Louis Goldkette’s (the younger) children emigrated to the USA. A grandchild, Jean Goldkette, whose mother Ancholine was born in Denmark, was educated as a pianist and became a well-known leader of a jazz band in the twenties. Louis Goldkette’s first cousin Francois, a son of Herman Goldkette, settled in Sweden and became the father of four boys, who became famous as the “4 Bronetts”, a group of clowns. They even changed their family name to Bronett. In the thirties, they founded Circus Scott, a well-known circus in Sweden which existed until 2004, led first by the widow of one of the four brothers. After her death, her son took over and later his son. Two of the “4 Bronetts” were married to two cousins of the Blumenfeld family. And one of the cousin’s mothers was from the German-Jewish Strassburger family, the fourth Jewish circus family mentioned in this article.